Role of Meritocracy in Strengthening Organizational Commitment among Medical Personnel at Brebes District Hospital - Susilowati Susilowati; Muhammad Fachruddin Arrozi Anastina Tahjoo (Lembaga Pengembangan Kinerja Dosen, 2026)
Organizational commitment is essential for maintaining hospital performance, service quality, and healthcare continuity. Preliminary data from Brebes Regional General Hospital shows that 35% of medical doctors face issues with low organizational commitment, which may negatively impact the institution's effectiveness. This study examines how meritocracy strengthens the effects of transformational leadership and work motivation on medical personnel's organizational commitment. A quantitative approach with causal research design was used to analyze the relationships among these variables. The sample included 72 doctors, selected through purposive sampling. Data were collected via structured questionnaires and analyzed using Moderated Regression Analysis (MRA) to assess both direct and moderating effects. The findings show that transformational leadership, work motivation, and meritocracy together significantly influence organizational commitment. Transformational leadership and work motivation each have a positive impact on organizational commitment. Additionally, meritocracy serves as a moderating factor, enhancing the connection between leadership and commitment, as well as work motivation and commitment. These results suggest that meritocratic systems based on competence, performance, and achievement improve leadership effectiveness and motivation, fostering greater commitment among medical staff. The study suggests that hospital management should implement meritocratic principles consistently in leadership and human resource practices, alongside developing transformational leadership and motivation strategies, to maintain high levels of organizational commitment among medical personnel.